Strategi Bisnis Business Model Canvas pada Bumdes-Mart Berkah - Agung Prawijaya; R. Hamdani Harahap; Erika Revida (PERSPEKTIF, 2021)
The purpose of this study was to see modern market development with the Franchise concept and in collaboration with third parties opens a partnership space in the management of Village Business Stores carried out by BUMDes managers. This study aims to analyze the implementation of the business strategy developed by BUMDes-Mart Berkah Jatimulyo Village, Pegajahan District, Serdang Bedagai Regency, using the business model canvas as a tool to identify existing business models. This research uses descriptive qualitative research methods, data collection techniques by conducting literature studies and research in the field. Data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions. The results obtained are in the form of a description of the nine elements in the business model consisting of customer segments, value proposition, customer relationships, customer segments, channels, revenue streams, cost structure, key activities, key resources, key partners. This business model will find out the weaknesses and strengths of a business that is being run and to find out what strategies can be implemented in the future. In addition to these aspects, the findings in this study are that there are factors that influence the business model canvas on BUMDes-Mart, namely in terms of market and financial segments.